Taking the long view: the development of the Well-being of Future Generations (Wales) Act - Eleanor Messham; Sally Sheard (Health Research Policy and Systems, 2020)
Abstract Background The Well-being of Future Generations (Wales) Act, 2015 (WFG Act), aims to change the ways of working in Wales to be sustainable for the future. Goals within the WFG Act include ‘a healthier Wales’, ‘a more equal Wales’ and ‘a more prosperous Wales’. Reviewing key factors that led to Wales enacting this ground-breaking legislation is worthwhile for other legislatures around the world that may wish to create policy for future generations. We suggest that the drive of individual politicians, events at the time and recent history were the most critical issues in developing a more nuanced piece of legislation – the WFG Act. Methods Ten interviews were conducted with those involved in the development of the WFG Act. Relevant documents were identified through systematic literature reviews and discussion with interviewees. Initial outcomes were tested against policy analysis frameworks, and Kingdon’s Multiple Stream Analysis was selected. Results Key ‘policy entrepreneurs’ were found to be important, along with growing evidence of the problems of climate change and recommendations for sustainable development in Wales. The importance of context and capitalising on global and local events by policy actors was significant. A supportive environment, including the third sector, community groups, cross-party backing, committed civil servants and a change of ministers helped with momentum. Discussion Policy-makers did not work directly with historians on developing the WFG Act. However, recent history was included with collaboration of the Wales Audit Office, who had evaluated the Welsh Government’s implementation of the duty to promote sustainable development. Sustainable, future-generation policies of other nations were also used to help shape the WFG Act. Kingdon’s Multiple Stream Analysis is a useful theory to interpret the timing and impact of this policy change. Conclusions The problem of climate change, suitable policy solutions, political support, timing and, most importantly, policy entrepreneurs were all significant in the development of the WFG Act. Due to multiple factors, policy-makers in Wales have legislated for the long term, placing sustainability and the well-being of present and future generations at the heart of public services and government.